Parasites of the Brazilian sandperch Pinguipes brasilianus Cuvier: A tool for stock discrimination in the Argentine Sea - Timi, Juan Tomas (2008)
The use of parasites as biological tags allowed the identification of three stocks of Brazilian sandperch Pinguipes brasilianus in the Argentine Sea. A total of 156 specimens caught during spring 2006, off the coasts of Buenos Aires Province (38°27′ S; 57°90′ W, n = 54), San Matías Gulf (42°S; 65°10′ W, n = 52) and Nuevo Gulf (42°09′ S; 64°05′ W, n = 50), were examined for parasites and 21 species were found, including monogeneans, digeneans, cestodes, nematodes, acanthocephalans and crustaceans. Diet analyses showed that Brazilian sandperch feed mainly on benthic macroinvertebrates, with differences in relative importance of main items between zones. Univariate analysis on parasite population descriptors, as well as a discriminant analysis, allowed the identification of discrete stocks in each zone, although a higher degree of similarity was observed between both Patagonian Gulfs. Northern samples were characterized by higher values of prevalence and abundance of Grillotia sp., Corynosoma australe and Scolex polymorphus. On the other hand, Trifur tortuosus and Opecoelidae gen. sp. were important in determining the position of Patagonian samples and were specially related to those from Nuevo Gulf, whereas none of the species was clearly related only to fish from San Matías Gulf. The size of the hosts is likely to influence the similarity among zones, with larger fish as better tools to discriminate stocks, probably because they harbour 'mature' assemblages shaped longer by differential environmental conditions and diet in each zone. Parasite species characteristic of sandperch from Buenos Aires Province, which display very low specificity among fish species in this area, have been previously identified as biological tags for other host species in these region, confirming their value as tags for stock delineation.